Ureterocutaneous fistula after kidney transplantation: A case report - Freitas, Andressa Paes Medeiros de; Lima, Gustavo Liberato David de; Almeida, João Ricardo Cunha Misson; Jardim, Valescka Aparecida Franco; Rocha, Vinicius Prata; Dezem, Beatriz Scarelli; Silveira, Gabriela Assunção M. e; Almeida, Lucas Pimenta de (Seven Editora, 2024)
INTRODUCTION: Renal replacement therapy (TRT) among the treatment modalities for chronic kidney disease is considered one of the best alternatives for managing the disease, since it improves the quality of life, survival and general long-term morbidity and mortality of patients in this context. Brazil ranks third in the world in the number of kidney transplants performed. However, kidney transplantation may have some clinical and surgical complications that need to be quickly identified, and if possible treated as soon as possible for a better patient outcome. The most prevalent urological complications after TRT involve fistulas, stenosis and reflux in the uretero-vesical anastomosis, which in strength and evidence D affect between 5 and 10% of patients submitted to different series and studies (CRANSTON D, LITTLE D. 2001). Although rarely lethal, these complications are an important cause of morbidity and have a direct correlation with chronic dysfunction and graft loss. In numerical terms, kidney transplantation accounts for about 70% of all organ transplants in the country today. The Mário Palmério University Hospital (MPHU) in the city of Uberaba-MG performed 17 kidney transplants in January 2023 alone. Therefore, this article aims to report a complication after a kidney transplant performed at the MPHU institution. The objective is to report a case of ureterocutaneous fistula in a patient undergoing kidney transplantation, who required a new approach with ureteral replantation. REPORT: Patient R.R.S, 35 years old, with down syndrome and chronic kidney disease, who underwent kidney transplantation on 01/30/2023, received a right kidney that had the presence of a cyst and was marsupialized in the bench surgery, ischemia time of 21 hours. The patient was implanted in the right iliac fossa using the Linch Gregoir technique, with no intraoperative complications. The patient progressed in the postoperative period with the use of vasoactive drugs for 48 hours. The patient presented diuresis in an indwelling urinary catheter only on the third postoperative day (POD). On the 16th day of the POD, it was necessary to re-approach due to the persistence of oliguria and dilatation of the ureter on control ultrasound. Intraoperatively, necrosis of the ureter implanted in the middle third was evidenced, and the pyelic-pelvic anastomosis was performed using the native ureter. The patient developed a considerable amount of diuresis in the postoperative period. On the 7th postoperative day of ureteral replantation, the patient had a higher output in a laminar tube drain than in an indwelling bladder catheter, and another approach was indicated, in which the presence of a fistula of the collecting system in the region of a previously marsupialized cyst was evidenced, and the patient was then submitted to fistula raffia and surgicel positioned. DISCUSSION: The main urological complications after kidney transplantation are: urinary obstruction, bladder fistula, urinary fistula due to ureter necrosis, and stenosis. In the case of fistulas, studies have shown that older donors may be related to the onset of this adversity, as well as increased cold ischemia time, the latter factor being present in the case described. In addition, the lack of standardization of the type of ureteral implant and the lack of studies addressing this topic allow us to question the possibility of a relationship between the type of technique chosen and the incidence of urinary fistulas. In addition, the appearance of fistula in the marsupialization of the cyst is something that has not yet been described in the medical literature, which demonstrates the demand for more research in the area, in order to achieve a higher degree of technical excellence for the benefit of transplant recipients. DOI:https://doi.org/10.56238/sevened2024.001-031